Effects of mechanical ventilation on gene expression profiles in renal allografts from brain dead rats - Hottenrott, Maximilia C.; Krebs, Jörg; Lücke, Thomas; Sticht, Carsten; Breedijk, Annette; Yard, Benito A.; Tsagogiorgas, Charalambos (Respiratory physiology & neurobiology, 2017)
Pathophysiological changes of brain death (BD) are impairing distal organ function and harming potential renal allografts. Whether ventilation strategies influence the quality of renal allografts from BD donors has not been thoroughly studied. 28 adult male Wistar rats were randomly assigned to four groups: 1) no brain death (NBD) with low tidal volume/low positive endexpiratory pressure (PEEP) titrated to minimal static elastance of the respiratory system (LVT/OLPEEP); 2) NBD with high tidal volume/low PEEP (HVT/LPEEP); 3) brain death (BD) with LVT/OLPEEP; and 4) BD with HVT/LPEEP. We hypothesized that HVT/LPEEP in BD leads to increased interleukin 6 (IL-6) gene expression and impairs potential renal allografts after six hours of mechanical ventilation. We assessed inflammatory cytokines in serum, genome wide gene expression profiles and quantitative PCR (qPCR) in kidney tissue. The influence of BD on renal gene-expression profiles was greater than the influence of the ventilation strategy. In BD, LVT ventilation did not influence the inflammatory parameters or kidney function in our experimental model.